2015
DOI: 10.1111/1365-2664.12555
|View full text |Cite
|
Sign up to set email alerts
|

Creating fen initiation conditions: a new approach for peatland reclamation in the oil sands region of Alberta

Abstract: 1.Reclaiming peatland ecosystems is challenging our understanding of how to rebuild functioning landscapes. Assisted succession may provide a practical approach to guide the reestablishment of peatlands in denuded landscapes. In Alberta, the majority of peatlands began as fens during the paludification process. This research focuses on creating fen initiation conditions to establish fen moss species on mineral sediment as an approach for peatland reclamation in the oil sands region. 2. In a field mesocosm expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 56 publications
(102 reference statements)
0
22
0
Order By: Relevance
“…In boreal rich fens, T. nitens is one of the most abundant and has the widest habitat niche breadth among true peatland moss species (Gignac, ; Vitt, Wieder, Scott, & Faller, ). The ability of T. nitens to establish and dominate is likely influenced by its resistance and resilience to submergence along with its tolerance of desiccation (Borkenhagen & Cooper, ; Goetz & Price, ; Manukjanová et al., ). Our results stress the importance of T. nitens in maintaining ecosystem function and resilience to drying and flooding disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…In boreal rich fens, T. nitens is one of the most abundant and has the widest habitat niche breadth among true peatland moss species (Gignac, ; Vitt, Wieder, Scott, & Faller, ). The ability of T. nitens to establish and dominate is likely influenced by its resistance and resilience to submergence along with its tolerance of desiccation (Borkenhagen & Cooper, ; Goetz & Price, ; Manukjanová et al., ). Our results stress the importance of T. nitens in maintaining ecosystem function and resilience to drying and flooding disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…They found shade increased regeneration for most species, and a high water table was ideal. In northern Alberta, Borkenhagen and Cooper () found that they could establish a range of fen bryophytes on mineral soil that mimicked the initial conditions under which fens formed that is further facilitated with peat amendments as tested on well pads (Gauthier unpublished data). These studies suggest great promise in creating habitat suitable for true moss establishment in restored fens.…”
Section: Peatland Types Being Restored Has Expandedmentioning
confidence: 99%
“…Two large‐scale fen reclamation projects have attempted to create watersheds and functioning peatland ecosystems on postoil sands extraction landscapes (Price et al ; Daly et al ). These projects have imported salvaged peat from donor wetlands and introduced plant propagules as soil seed banks, seed, vascular plants grown from seed in nurseries, and moss fragment transfer approaches (Borkenhagen & Cooper ). The potential effects of process water from oil sands, which can have high concentrations of toxins, strongly influence fen plant survival (Pouliot et al , ).…”
Section: New Approaches Developed For Restoring Additional Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation
“…A central component of the landscape reclamation strategy is the overall approach and feasibility of constructing heterogeneous boreal landscapes of lowland wetlands and upland forests on previously mined sites (Alberta Environment, 2010;Devito, Mendoza, & Qualizza, 2012). Although a focus of recent reclamation research efforts has been on the creation of wetlands (Borkenhagen & Cooper, 2016;Ketcheson et al, 2016;Mollard, Roy, & Foote, 2015;Nicholls, Carey, Humphreys, Clark, & Drewitt, 2016), earlier and ongoing reclamation activities have focussed on forests and aspects of forest establishment including soil water dynamics (Carrera-Hernández, Mendoza, Devito, Petrone, & Smerdon, 2012;Huang, Barbour, & Carey, 2015), vegetation cover (Pinno & Hawkes, 2015;Rowland, Prescott, Grayston, Quideau, & Bradfield, 2009), soil bacteria (Quideau, Swallow, Prescott, Grayston, & Oh, 2013), nutrient fixation (Kwak, Chang, Naeth, & Schaaf, 2015;Yan et al, 2012), and saline toxicity (Kelln, Barbour, & Qualizza, 2008;Lilles, Purdy, Macdonald, & Chang, 2012).…”
Section: Introductionmentioning
confidence: 99%